Early physiotherapy experience with a biodegradable polyurethane dermal substitute: Therapy guidelines for use. Issue 5 (August 2021) - Schmitt, Brads; Heath, Kathryn; Kurmis, Rochelle; Klotz, Tanja; Wagstaff, Marcus J.D.; Greenwood, John
Highlights: Understanding capabilities and limitations of a new dermal substitute takes time. Range of motion and mobilisation can safely occur early during the integration phase. Scar assessment indicated good scar cosmetic outcomes. Good return to function in the joints assessed. Therapy guidelines have been developed based on experiences to date. Abstract: Objective: The purpose of this study was to investigate and develop range of motion (ROM) and mobilisation guidelines in adult patients where a newly developed synthetic dermal substitute was applied in our adult burn centre. Method: A retrospective case note audit was conducted on the first 20 acute burn injured patients who had a synthetic dermal substitute applied. Data collected included days to commencement of ROM, days to clearance for mobilisation, and joint ROM achieved after dermal substitute application (prior to delamination) and after split skin grafting (SSG) for the elbow, knee and shoulder joints. Scar assessments were completed at 12 months after injury using two scar assessment scales. Results: Clearance to mobilise occurred at mean 10.4 and 4.9 days after dermal substitute and after skin graft application to lower limbs respectively. ROM commenced at a mean of 9.9 (upper limbs) and 12.7 (lower limbs) days after dermal substitute application. Following skin grafting, ROM commenced at a mean of 6.6 and 6.5 days for upper limbs and lower limbs respectively. Prior to dermal substitute delamination mean flexion at the knee (86.3°), elbow (114.0°) and shoulder (143.4°) was achieved. Mean ROM continued to improve after grafting with knee (133.2°), elbow (126.1°) and shoulder (151.0°) flexion approaching normal ROM in most cases. Mean extension of the elbow (-4.6°) was maintained close to normal levels after skin grafting. There were no recorded instances of knee extension contracture. Patient and Observer Scar Assessment Scale and Matching Assessment of Photographs of Scars scores indicated good cosmetic outcomes with relatively low levels of itch and minimal pain reported at 12 months after injury. Conclusion: A steep learning curve was encountered in providing therapy treatment for patients managed with this relatively new synthetic dermal substitute. Trends indicated that as experience with this new dermal substitute grew, patients progressed toward active therapy earlier. A guideline for therapy treatment has been developed but will continue to be evaluated and adjusted when required.